Character Education In Playing Song Material With SAVI Approach For The Elementary School Students - Endang Sri Maruti (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
In learning tembang dolanan (songs for playing) there is character education, yetsince the teaching system in schools, especially in primary schools is still very minimal, the character education is rarely touched. For that need a strategy that must be done by teacher with the intention of character education can be conveyed well through material tembang dolanan. One of the efforts that can be done is with the development of teaching materials SAVI approach on materials nembang dolanan fourth grade elementary school in which in the textbook there is also character education in accordance with the approach SAVI. The result of the analysis shows that in the teaching materials in the form of student textbooks SAVI approach on the material of the dolanan tembanganan for grade 4 elementary school there is character education in every step SAVI. In somatic learning, students are invited to discipline, hard work, friendly or communicative, love peace, democratic, and responsibility, on learning auditory students are invited to independent, tolerance, and add curiosity, the visual learning students are invited to always love the land water, reading, and environmental cares, and on students intellectual learning are encouraged to be more religious and creative.